Correlation between CCL2, CALCA, and CX3CL1 gene polymorphisms and chronic pain after cesarean section in Chinese Han women: A case control study. Issue 34 (August 2019) - Ma, Guoping; Yang, Jingli; Zhao, Bange; Huang, Chengquan; Wang, Rui
Abstract: Objective: Postoperative chronic pain is characterized by high incidence, long duration, and complex pathogenesis. The purpose of this study was to investigate the correlation between the single nucleotide polymorphisms of the CCL2 gene rs4586 (g.5974T>C), CALCA rs3781719 (−692T>C), CX3CL1 rs614230 (2342C>T), and the risk of postoperative chronic pain in Chinese Han women. Methods: We analyzed the CCL2 gene rs4586, CALCA rs3781719, CX3CL1 rs614230 single nucleotide polymorphism (SNPs) of 350 Chinese Han women with chronic postsurgical pain (CPSP) 6 months after cesarean section and 350 healthy women without chronic pain (HC). The levels of CCL2, CALCA, and CX3CL1 in serum were detected by enzyme-linked immunosorbent assay (ELISA). Results: The CCL2 rs4586 T allele and the CX3CL1 gene rs614230C allele were protective factors for CPSP risk (adjusted OR = 0.766, 95% CI: 0.675–0.865 and OR = 0.336, 95% CI: 0.644–0.835). The CALCA gene rs3781719C allele was a risk factor for CPSP (adjusted OR = 1.273, 95% CI: 1.125–1.424). CCL2 rs4586, CX3CL1 gene rs614230, and CALCA gene rs3781719 locus gene polymorphisms were associated with serum CCL2, CX3CL1, and CALCA protein levels. Conclusion: Our results support that CCL2 gene rs4586, CALCA rs3781719, CX3CL1 rs614230 gene polymorphism are associated with the occurrence of chronic pain after cesarean section in Chinese Han women.